Effect of Larger Pore Size on the Sorption Properties of Isoreticular Metal–Organic Frameworks with High Number of Open Metal Sites. Issue 59 (24th September 2020) - Dietzel, Pascal D. C.; Georgiev, Peter A.; Frøseth, Morten; Johnsen, Rune E.; Fjellvåg, Helmer; Blom, Richard
Abstract: Four isostructural CPO‐54‐M metal‐organic frameworks based on the larger organic linker 1, 5‐dihydroxynaphthalene‐2, 6‐dicarboxylic acid and divalent cations (M=Mn, Mg, Ni, Co) are shown to be isoreticular to the CPO‐27 (MOF‐74) materials. Desolvated CPO‐54‐Mn contains a very high concentration of open metal sites, which has a pronounced effect on the gas adsorption of N2, H2, CO2 and CO. Initial isosteric heats of adsorption are significantly higher than for MOFs without open metal sites and are slightly higher than for CPO‐27. The plateau of high heat of adsorption decreases earlier in CPO‐54‐Mn as a function of loading per mole than in CPO‐27‐Mn. Cluster and periodic density functional theory based calculations of the adsorbate structures and energetics show that the larger adsorption energy at low loadings, when only open metal sites are occupied, is mainly due to larger contribution of dispersive interactions for the materials with the larger, more electron rich bridging ligand. Abstract : Metal–organic frameworks with coordinatively exposed metal cations perform extraordinarily well in low‐pressure sorption processes. CPO‐54‐Mn is isoreticular to the heavily studied CPO‐27/MOF‐74 materials. It has a honeycomb structure with a larger pore and the second highest number of open metal sites. The difference in pore size and chemical structure affects the behavior of the two isostructural compounds on adsorption of CO2, H2 and CO.